Effects of acquired vestibular pathology on the organization of mouse exploratory behavior - Mark T. Banovetz; Rami I Lake; Ashley A. Blackwell; Jenna R. Osterlund Oltmanns; Ericka A. Schaeffer; Ryan M Yoder; Douglas G. Wallace (Experimental Brain Research, 2021)

Neonatal Multisensory Processing in Preterm and Term Infants Predicts Sensory Reactivity and Internalizing Tendencies in Early Childhood - Nathalie L. Maitre; Alexandra P. Key; James C. Slaughter; Paul J. Yoder; Mary Lauren Neel; Céline Richard; Mark T. Wallace; Micah M. Murray (Brain Topography, 2020)
Multisensory processes include the capacity to combine information from the different senses, often improving stimulus representations and behavior. The extent to which multisensory processes are an innate capacity or instead require experience with environmental stimuli remains debated. We addressed this knowledge gap by studying multisensory processes in prematurely born and full-term infants. We recorded 128-channel event-related potentials (ERPs) from a cohort of 55 full-term and 61 preterm neonates (at an equivalent gestational age) in response to auditory, somatosensory, and combined auditory-somatosensory multisensory stimuli. Data were analyzed within an electrical neuroimaging framework, involving unsupervised topographic clustering of the ERP data. Multisensory processing in full-term infants was characterized by a simple linear summation of responses to auditory and somatosensory stimuli alone, which furthermore shared common ERP topographic features. We refer to the ERP topography observed in full-term infants as “typical infantile processing” (TIP). In stark contrast, preterm infants exhibited non-linear responses and topographies less-often characterized by TIP; there were distinct patterns of ERP topographies to multisensory and summed unisensory conditions. We further observed that the better TIP characterized an infant’s ERPs, independently of prematurity, the more typical was the score on the Infant/Toddler Sensory Profile (ITSP) at 12 months of age and the less likely was the child to the show internalizing tendencies at 24 months of age. Collectively, these results highlight striking differences in the brain’s responses to multisensory stimuli in children born prematurely; differences that relate to later sensory and internalizing functions.

Consensus guidelines for the use and interpretation of angiogenesis assays - Patrycja Nowak-Sliwinska; Kari Alitalo; Elizabeth Allen; Andrey Anisimov; Alfred C. Aplin; Robert Auerbach; Hellmut G. Augustin; David O. Bates; Judy R. van Beijnum; R. Hugh F. Bender; Gabriele Bergers; Andreas Bikfalvi; et al. (Angiogenesis, 2018)

Optimal Scaling of Aftershock Zones using Ground Motion Forecasts - John Max Wilson; Mark R. Yoder; John B. Rundle (Pure and Applied Geophysics, 2018)

Earthquakes and Multi-Hazards Around the Pacific Rim, Vol. II: Introduction - Charles A. Williams; Zhigang Peng; Yongxian Zhang; Eiichi Fukuyama; Thomas Goebel; Mark R. Yoder (Pure and Applied Geophysics, 2018)

Earthquakes and Multi-hazards around the Pacific Rim, Vol. 1: Introduction - Yong-Xian Zhang; Thomas Goebel; Zhigang Peng; Charles Williams; Mark Yoder; John Rundle (Pure and Applied Geophysics, 2017)

Parametrizing Physics-Based Earthquake Simulations - Kasey W. Schultz; Mark R. Yoder; John M. Wilson; Eric M. Heien; Michael K. Sachs; John B. Rundle; Don L. Turcotte (Pure and Applied Geophysics, 2017)

Spatial Evaluation and Verification of Earthquake Simulators - John Max Wilson; Mark R. Yoder; John B. Rundle; Donald L. Turcotte; Kasey W. Schultz (Pure and Applied Geophysics, 2017)

Record-Breaking Intervals: Detecting Trends in the Incidence of Self-Similar Earthquake Sequences - Mark R. Yoder; John B. Rundle (Pure and Applied Geophysics, 2015)

E-DECIDER: Using Earth Science Data and Modeling Tools to Develop Decision Support for Earthquake Disaster Response - Margaret T. Glasscoe; Jun Wang; Marlon E. Pierce; Mark R. Yoder; Jay W. Parker; Michael C. Burl; Timothy M. Stough; Robert A. Granat; Andrea Donnellan; John B. Rundle; Yu Ma; Gerald W. Bawden; et al. (Pure and Applied Geophysics, 2015)

Near-Field ETAS Constraints and Applications to Seismic Hazard Assessment - Mark R. Yoder; John B. Rundle; Margaret T. Glasscoe (Pure and Applied Geophysics, 2015)

Statistical Variability and Tokunaga Branching of Aftershock Sequences Utilizing BASS Model Simulations - Mark R. Yoder; Jordan Van Aalsburg; Donald L. Turcotte; Sergey G. Abaimov; John B. Rundle (Pure and Applied Geophysics, 2013)

Amyloid pathway-based candidate gene analysis of [11C]PiB-PET in the Alzheimer’s Disease Neuroimaging Initiative (ADNI) cohort - Shanker Swaminathan; Li Shen; Shannon L. Risacher; Karmen K. Yoder; John D. West; Sungeun Kim; Kwangsik Nho; Tatiana Foroud; Mark Inlow; Steven G. Potkin; Matthew J. Huentelman; David W. Craig; et al. (Brain Imaging and Behavior, 2012)

No evidence for root-mediated allelopathy in Centaurea solstitialis, a species in a commonly allelopathic genus - Bo Qin; Jennifer A. Lau; Joseph Kopshever; Ragan M. Callaway; Heather McGray; Laura G. Perry; Tiffany L. Weir; Mark W. Paschke; Jose L. Hierro; John Yoder; Jorge M. Vivanco; Sharon Strauss (Biological Invasions, 2007)

Modeling Ocean Ecosystems: The PARADIGM Program - Lewis Rothstein; John Cullen; Mark Abbott; Eric Chassignet; Ken Denman; Scott Doney; Hugh Ducklow; Katja Fennel; Mick Follows; Dale Haidvogel; Eileen Hofmann; David Karl; et al. (Oceanography, 2006)